Resonant frequency in polypropylene fibre reinforced concrete (PFRC) with pozzolanic materials - Leung, Hau Y.; Balendran, Ramapillai V. (Journal of Civil Engineering and Management, 2002)
In this study, the resonant frequency of polypropylene fibre reinforced concrete (PFRC) under three different curing conditions was investigated and the influences of fly ash (PFA) and silica fume (SF) on PFRC under the same curing condition were also studied. The experiments were carried out in the Heavy Laboratory of City University of Hong Kong. Four types of concrete mixes were tested. A total of 24 concrete specimens were prepared. Test results show that the resonant frequency can be affected by the presence of polypropylene fibres, partial replacement of cement by silica fume or pulverized fly ash, and curing condition.Frist Published Online: 30 Jul 2012